Artimi įstrigusių pilvo sienos išvaržų gydymo rezultatai - Stanaitis, Juozas; Saltanavičius, Robertas; Povilavičius, Jonas; Stašinskas, Algimantas (Lietuvos chirurgija, 2010)
Juozas Stanaitis, Robertas Saltanavičius, Jonas Povilavičius, Algimantas StašinskasVilniaus universitetas, Vilniaus greitosios pagalbos universitetinė ligoninė,Šiltnamių g. 29, LT-04130 VilniusEl. paštas: juozas.stanaitis@mf.vu.ltĮstrigusios išvaržos gydymo rezultatai nėra patenkinami. Jie daugiausia priklauso nuo laiku atliktos diagnostikos ir gydymo. Todėl šiame straipsnyje nutarta apžvelgti ir apibendrinti Vilniaus greitosios pagalbos universitetinės ligoninės įstrigusios išvaržos gydymo dešimties metų rezultatus.Reikšminiai žodžiai: įstrigusi išvarža, gydymas, rezultatai.Early results of incarcerated abdominal wall hernia repairJuozas Stanaitis, Robertas Saltanavičius, Jonas Povilavičius, Algimantas StašinskasVilnius University, Vilnius University Emergency Hospital,Šiltnamių str. 29, LT-04130 Vilnius, LithuaniaE-mail: juozas.stanaitis@mf.vu.ltThe incarcerated hernia still remains an urgent problem. In the cases of strangulated hernia almost it is important damaging of intraabdominal organs, especially bowels, because it predetermine the course of disease in distance. This article is prospective estimation of treatment results of incarcerated hernias, also complicated with bowel necrosis. According to the data from case history we look over 621 patients had undergone operation because of incarcerated abdominal wall hernias during last ten years. This amount form 1/5 of all patients had operated on due to abdominal wall hernias. All cases are divided up in two groups: incarcerated hernia without damage of bowel (n = 556) and incarcerated hernia with bowel's necrosis (n = 65). Patient's age, duration of illness, localisation of hernia, pathological changing in strangulated bowels, operation's methods, postoperative complications and cause of deaths were taking into consideration. 17 patients had died among 621 were operated on because of incarcerated hernia, the rate of mortality was 2.7 %. There were 10 deaths among 65 patients bowel necrosis had been founded (15.4 %). In other 556 patients group with vital incarcerated organs where hernioplasty were performed deaths had occurred in 7 cases – 1.3 %.Key words: incarcerated hernia, surgery, results.